Measurement of Cancer Cell Growth Heterogeneity through Lentiviral Barcoding Identifies Clonal Dominance as a Characteristic of In Vivo Tumor Engraftment. - Olivier Nolan-Stevaux; Donato Tedesco; Seamus Ragan; Mikhail Makhanov; Alex Chenchik; Astrid Ruefli-Brasse; Kim Quon; Paul D Kassner (PLoS ONE, 2013)
Advances in the fields of cancer initiating cells and high-throughput in vivo shRNA screens have highlighted a need to observe the growth of tumor cells in cancer models at the clonal level. While in vivo cancer cell growth heterogeneity in xenografts has been described, it has yet to be measured. Here, we tested an approach to quantify the clonal growth heterogeneity of cancer cells in subcutaneous xenograft mouse models. Using a high-throughput sequencing method, we followed the fate in vitro and in vivo of ten thousand HCT-116 cells individually tagged with a unique barcode delivered by lentiviral transduction. While growth in vitro was less homogeneous than anticipated, we still find that 95% of the final cells derived from 80% of the original cells. In xenografts, however, 95% of the retrieved barcoded cells originated from only 6% of the initially injected cells, an effect we term "clonal dominance". We observed this clonal dominance in two additional xenograft models (MDA-MB-468 and A2780(cis)) and in two different host strains (NSG and Nude). By precisely and reproducibly quantifying clonal cancer cell growth in vivo, we find that a small subset of clones accounts for the vast majority of the descendant cells, even with HCT-116, a cell line reported to lack a tumor-initiating compartment. The stochastic in vivo selection process we describe has important implications for the fields of in vivo shRNA screening and tumor initiating cells.